Inducción de proestro prolongado en vacas en anestro en condiciones tropicales: Una alternativa terapéutica (2022)
The objective of the work was to know the effect of the prolongation of proestrus in cows in anestrus with more than 90 days open, under tropical conditions, on the pregnancy rate after fixed-time artificial insemination (FTAI) compared to a conventional protocol. An experiment was carried out where 8 cows were selected and randomly divided into two equal groups (4 animals per group) performing a different protocol for each one. Group 1 (G1) with prolonged proestrus protocol, Day 0 placement of the intravaginal implant of progesterone (DIP4) (dispocel 0.6 gr) and estradiol benzoate (sincrodiol, 2 ml) intramuscularly (IM); On day 6, removal of DIP4 and IM injection of Cloprostenol (sincrocio, 2 ml) and 500 IU of equine chorionic gonadotropin (eCG) (Sincro eCG, 2.5 ml) are performed; Day 9 is applied via IM, buserelin acetate (sincroforte 2.5 ml) and 16 hours later IATF. Group 2 (G2) with conventional protocol, placement of DIP4 (dispocel 0.6 gr) and 2 ml of sincrodiol intramuscularly (IM) was performed; On day 8, DIP4 was removed and IM injection of 2 ml of sincrocio; On day 10, 2.5 ml of sincroforte are applied and IATF is performed at the same time. The pregnancy rate in G1 was 25% (1/4) and in G2 it was 50% (2/4); therefore, it was concluded that the pregnancy rate did not show significant differences in both groups; also the use of eCG in G1 did not influence the pregnancy rate compared to G2 in which eCG was not used, however, the study does not have enough animals to conclude statistically significant results. Keywords. prolonged proestrus, anestrus, tr